Ability to Maintain and Improve Health and Socio-Demographic Correlates among Children in Albania - Muja Herion; Vasil Suela; Toçi Dorina; Clemens Timo; Brand Helmut; Burazeri Genc (Sciendo, 2024)
Our aim was to assess the level and socio-demographic correlates of the ability to maintain health among children in Albania, a post-communist country in the Western Balkans.